2012
DOI: 10.1007/s00726-012-1225-y
|View full text |Cite
|
Sign up to set email alerts
|

Taurine ameliorates alloxan-induced diabetic renal injury, oxidative stress-related signaling pathways and apoptosis in rats

Abstract: Hyperglycemia-induced oxidative stress plays a vital role in the progression of diabetic nephropathy. The renoprotective nature of taurine has also been reported earlier; but little is known about the mechanism of this beneficial action. The present study has, therefore, been carried out to explore in detail the mechanism of the renoprotective effect of taurine under diabetic conditions. Diabetes was induced in rats by alloxan (single i.p. dose of 120 mg/kg body weight) administration. Taurine was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 71 publications
(72 reference statements)
4
56
0
1
Order By: Relevance
“…The release of the mediators TNF-α and IL-1β starts at the beginning of reperfusion and increases during the early phase of I/R in kidney (6,7). The surge of oxygen to low oxygenated tissues causes increased production of ROS by TNF-α and IL-1β (8). The apoptosis pathway is activated as a result of mitochondrial damage caused by ROS.…”
Section: Introductionmentioning
confidence: 99%
“…The release of the mediators TNF-α and IL-1β starts at the beginning of reperfusion and increases during the early phase of I/R in kidney (6,7). The surge of oxygen to low oxygenated tissues causes increased production of ROS by TNF-α and IL-1β (8). The apoptosis pathway is activated as a result of mitochondrial damage caused by ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Taurine, by virtue of its antioxidant activity, has been shown to play a crucial role as a cytoprotectant and in the attenuation of apoptosis [17]. There is a growing consensus that oxidative stress is linked to mitochondrial dysfunction and that the beneficial effects of taurine are due to its antioxidant properties [18], added to its ability to improve mitochondrial function by stabilizing the electron transport chain and inhibiting the generation of reactive oxygen species [19].…”
mentioning
confidence: 99%
“…As for diabetes, its marked hyperglycemia and hyperlipidemia induced by absolute or relative insulin deficiency evokes a lot of free radical generation and then induces cell apoptosis through caspase-9-dependent pathway [33]. Meanwhile, diabetes is regarded as an inflammatory process with the production of inflammatory mediators such as TNF-a and interleukin-6 [34], therefore, it would also initiate a caspase-8-dependent apoptotic pathway. Our results showed that the activity of caspase-8 was significantly increased from the 4th week in diabetic rats, while the activity of caspase-9 was significantly increased from the 12th week.…”
Section: Discussionmentioning
confidence: 99%